Self-Care Membantu Kesehatan Mental Individu - Ferdy Muzzamil; Tugimin Supriyadi; Siti Masitoh (Jurnal Kesehatan, 2026)
Mental health has become an essential aspect of life, especially in the face of increasing life pressures. One approach that has gained popularity is self-care, which refers to activities individuals engage in to maintain their physical, emotional, and psychological well-being. This study aims to explore the impact of self-care on mental health, particularly in preventing emotional disorders. The research method used is a case study with a literature review approach, examining recent journals related to self-care and mental health. The results of the literature review show that activities such as meditation, exercise, and stress management are effective in reducing anxiety and depression, while improving psychological well-being. Additionally, social support, especially from family and friends, plays a crucial role in strengthening self-care behaviors. This study also reveals that young people, particularly students, need education and support to incorporate self-care into their daily lives. Based on the analysis of five relevant articles, it can be concluded that regular self-care practices can enhance mental health and prevent long-term psychological disorders. Therefore, self-care is an effective strategy for maintaining individual well-being.